THE EFFECT OF SUPPORTIVE GROUP THERAPY ON THE BURDEN AND COPING MECHANISMS IN CARING FOR FAMILY MEMBERS WHO SUFFER SCHIZOPHRENIA - Liyanovitasari Liyanovitasari; Noor Hamdani; Asti Melani Astari (Faculty of Nursing, Universitas Jember, 2017)
Schizophrenia is a psychiatric illness that causes the burden and maladaptive coping mechanism on the family. The burden and maladaptive coping mechanisms have an impact on the quality of family life and the ability of families to care for schizophrenic patients. The purpose of this study was to prove the effect of supportive group therapy on the burden and coping mechanisms in caring for family members who suffer schizophrenia. The design of this research was a pretest-posttest quasi-experimental study with control group design. The number of samples was 14 in the treatment group and 15 in the control group with purposive sampling. Variable of burden was measured with the Zarit Burden Interview (ZBI) and the coping mechanism was assessed by using Brief COPE Inventory (BCI). This supportive therapy was performed in 4 sessions with a total of 6 meetings. The results showed that there were significant differences on burden values and coping mechanisms before and after supportive therapy in the treatment group (p-value= 0.000). In the control group, there was a significant difference on the value of burden before and after health counseling (p-value =0.010), but there was no difference of coping mechanism value before and after health counseling (p-value=0.225). There were significant differences on the burden value (p-value=0.002) and coping mechanisms (p-value= 0.001) between treatment and control group. dr Rehatta Hospital is expected to facilitate the formation of peer support group in the psychiatry clinic so mental health in the family can be achieved.